The Chinese Ethnic Political Participation In Indonesian Political Development In Soe Hok Gie Film (Semiotics Study by Charles Sanders Pierce) - Singgih Dwi Nirwanto; Andhita Risko Faristiana (Pusat Riset dan Inovasi Nasional, 2023)
The post-reform era became public and government awareness of ethnic Chinese. This is evidenced by President Abdurrahman Wahid's decree to relax ethnic Chinese activities. Because in the Old Order, there was a government policy that was anti-Chinese sentiment. There is even a ban on foreigners to trade in Indonesia, as well as ethnic Chinese who become looting and mob rage, victims of sexual violence and so on. Through this Soe Hok Gie film, it depicts the participation of ethnic Chinese in solving the problem of government authoritarianism and saving Indonesia from the economic crisis. In this studyThis type of research uses library research, with a communication approach that uses media text analysis. The data collection technique in this study uses the semiotic analysis research method of Charles Sanders Peirce. The method uses Sign, Object and Interpretant to explain the content of a film.From the film Soe Hok Gie, this research has found themeaning of Sign, Object and Interpretant of ethnic Chinese political participation in the film Soe Hok Gie based on Charles Sander Peirce's semiotic theory. Finding an analysis of Sign, Object and Interpretant of ethnic Chinese political participation in political developments in Indonesia in the film Soe Hok Gie